2013
DOI: 10.1038/ng.2776
|View full text |Cite
|
Sign up to set email alerts
|

Truncating mutations of MAGEL2 cause Prader-Willi phenotypes and autism

Abstract: Prader-Willi Syndrome (PWS) is caused by the absence of paternally expressed, maternally silenced genes at 15q11-q13. We report four individuals with truncating mutations on the paternal allele of MAGEL2, a gene within the PWS domain. The first subject was ascertained by whole genome sequencing analysis for PWS features. Three additional subjects were identified by reviewing results of exome sequencing of 1248 cases in a clinical laboratory. All four subjects had autism spectrum disorder (ASD), intellectual di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
267
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(276 citation statements)
references
References 27 publications
4
267
1
4
Order By: Relevance
“…Recently, truncating mutations of MAGEL2 were also associated with PWS. 20 The discussion regarding expression of SNORD115 by non-neuronal cells can be applied to MAGEL2. Therefore, like for SNORD115, MAGEL2 expression could not be tested here.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, truncating mutations of MAGEL2 were also associated with PWS. 20 The discussion regarding expression of SNORD115 by non-neuronal cells can be applied to MAGEL2. Therefore, like for SNORD115, MAGEL2 expression could not be tested here.…”
Section: Discussionmentioning
confidence: 99%
“…In each case, the volunteer was counseled for the family risk and encouraged to contact at risk family members who may benefit from focused genetic studies. Three of the families have reported that they have had their familial genetic diagnosis resolved at this time [paraganglioma (49), Prader-Willi syndrome (50,51), and ankylosing spondylitis (AS) (52)]. One additional family is under study [Tourette syndrome (53)].…”
Section: Incorporation Of Three-generation Pedigrees Into the Geneticmentioning
confidence: 99%
“…5 The Magel2 KO mouse is now considered a mouse model for PWS and autism spectrum disorder (ASD) because truncated mutations in the Magel2 gene have been reported in some patients with ASD. 6 Restricted production of mature OXT despite normal prohormone production was detected specifically in the hypothalamus of the Magel2 KO pups. Altogether, these data suggest that OXT is involved in the pathophysiology of PWS and ASD.…”
mentioning
confidence: 99%